The use of egg shells to produce Cathode Ray Tube (CRT) glass foams - Fernandes, Hugo R.
Cleaned Cathode Ray Tube (CRT) (panel and funnel) waste glasses produced from dismantling TV and PC colour kinescopes were used to prepare glass foams by a simple and economic processing route, consisting of a direct heating of glass powders at relatively low temperatures (600-800 degrees C). This study reports on the feasibility of producing glass foams using waste egg shells as an alternative calcium carbonate-based (95 wt%) foaming agent derived from food industry. The foaming process was found to depend on a combination of composition, processing temperature and mixture of raw materials (glass wastes). Hot stage microscopy (HSM), X-ray diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize foams and evaluate the foaming ability and the sintering process. The experimental compositions allowed producing well sintered glass foams with suitable properties for some functional applications with environmental benefits such as: (1) reduced energy consumption because of the low heat treatment temperatures used; and (2) materials produced exclusively from residues. (C) 2013 Elsevier Ltd and Techna Group S.r.l. All rights reserved.